Factors Associated with Ruptured Ectopic Pregnancy: A 10-Year Review at a District Hospital in Ghana. (7th March 2022) - Sefogah, Promise E.; Oduro, Nana E.; Swarray-Deen, Alim; Nuamah, Hanson G.; Takyi, Raphael B.; Nuamah, Mercy A.; Oppong, Samuel A.
Abstract : Background . Approximately 1–2% of all pregnancies are ectopic. Despite a decline in ectopic pregnancy-related mortality, there is still a paucity of information on the factors associated with clinical presentation and outcomes in Sub-Saharan Africa which is essential in determining the most appropriate treatment modalities. Methods . We performed a ten-year retrospective chart review of cases of ectopic pregnancies managed at the Lekma hospital and assessed them for peculiar risk factors, clinical presentation, and outcomes. Associations between patients' sociodemographic characteristics, clinical presentation, and treatment outcome were evaluated using multiple logistic regression and reported as adjusted odds ratios (AOR). The confidence interval (CI) was set at 95%, and a p value <0.05 were considered significant. Results . Over the ten-year period, there were 115 ectopic pregnancies and 14, 450 deliveries (7.9/1, 000). The mean age ± standard deviation of the 115 patients was 27.61 ± 5.56. More than half of the patients were single (59/115, 51.3%). The majority (71.3%) of the patients presented with a ruptured ectopic pregnancy. After adjusting for covariates, the odds of an ectopic pregnancy presenting as ruptured among single patients was 2.63 times higher than that of married patients (AOR = 3.63, 95% CI: 1.33–9.93, p = 0.01 ). Ectopic pregnancies located in the isthmic region of the tube had a 77% lower odds of presenting as ruptured than those located in the ampullary region (AOR = 0.23, 95% CI: 0.07–0.74, p = 0.01 ). The odds of rupturing were 1.69 times increased for every additional week after the missed period (AOR = 2.69, 95% CI: 1.56–4.64, p < 0.01 ). No mortalities were reported as a result of an ectopic pregnancy. Conclusion . Most of the cases of ectopic pregnancy presented ruptured. Marital status and period of amenorrhoea were significantly associated with rupture.